1991
DOI: 10.1159/000200697
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically Generated Extracorporeal Shock Wave Lithotripsy and Adjuvant Combined Oral Litholysis for Therapy of Symptomatic Gallbladder Stones

Abstract: A prospective study was conducted to evaluate effectivity, problems and adverse effects of extracorporeal shock wave lithotripsy (ESWL) using a newly developed electromagnetic biliary lithotriptor (Lithostar Plus, Siemens, Erlangen, FRG) for the treatment of selected patients presenting with symptomatic cholecystolithiasis. In addition to generally accepted criteria for the selection of patients, gallbladder contractility was established and pigment stones were excluded by computed tomography (CT). 80 out of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…By combining both techniques, initial studies suggested that higher success rates could be possible [70,71]. Considering the increased cost and risk caused by directly cannulating the gallbladder, adjuvant therapy with cheno-and/or ursodeoxycholic acid was introduced as a safer modality [72,73]. Yet, complications including the risk of biliary obstruction, pancreatitis, or acute cholecystitis as consequences of successful stone fragmentation remained high [73][74][75][76].…”
Section: Treatmentmentioning
confidence: 99%
“…By combining both techniques, initial studies suggested that higher success rates could be possible [70,71]. Considering the increased cost and risk caused by directly cannulating the gallbladder, adjuvant therapy with cheno-and/or ursodeoxycholic acid was introduced as a safer modality [72,73]. Yet, complications including the risk of biliary obstruction, pancreatitis, or acute cholecystitis as consequences of successful stone fragmentation remained high [73][74][75][76].…”
Section: Treatmentmentioning
confidence: 99%